Penguatan Kapasitas Aparatur Desa dalam Pengelolaan Aset Desa melalui Pelatihan Manajemen Aset di Desa Sukabares Kabupaten Serang - Maulana Yusuf; Rahmawati Rahmawati; Ardiyansah Ardiyansah; Ipah Ema Jumiati (WINDRADI: Jurnal Pengabdian Masyarakat, 2026)
Village asset management is an essential component of village governance that supports accountability, transparency, and the optimal utilization of local resources. However, village officials often face challenges related to asset inventory, administration, legal status, and asset utilization in accordance with applicable regulations. This community service program aimed to strengthen the capacity of village officials in managing village assets through asset management training conducted in Sukabares Village, Waringin Kurung District, Serang Regency. The program was implemented through educational sessions, training workshops, interactive discussions, and practical assistance in preparing village asset administration documents. The training materials covered fundamental concepts of asset management, asset inventory procedures, legal audits, asset valuation, asset optimization strategies, as well as monitoring and control mechanisms. Participants included village officials, members of the Village Consultative Body (BPD), village asset managers, and community representatives. The results demonstrated an improvement in participants’ understanding of proper village asset governance, particularly regarding asset recording procedures, ownership identification, and inventory administration practices. Furthermore, participants were able to identify key challenges in village asset management and formulate practical solutions to address existing issues. The program contributed positively to enhancing institutional capacity and promoting more accountable, transparent, and sustainable village asset governance. The findings indicate that capacity-building initiatives through training can serve as an effective strategy to improve village asset management practices and support good governance at the village level.